2018
DOI: 10.1186/s12902-018-0317-4
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk reduction over time in patients with diabetes or pre-diabetes undergoing bariatric surgery: data from a single-center retrospective observational study

Abstract: BackgroundBariatric surgery is effective in remission of obesity comorbidities. This study was aimed at comparing CVD risk between morbidly obese patients with type 2 diabetes and pre-diabetes before and after bariatric surgery as well as assessing comorbidities.MethodsThis is a retrospective observational study with 105 patients with type 2 diabetes (DMbaseline) and prediabetes (preDMbaseline) who underwent Roux-en-Y gastric bypass. Data were collected preoperative and then at 3,6,12,18,24,36,48, and 60 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 27 publications
(23 reference statements)
4
16
0
1
Order By: Relevance
“…Improvement in glycaemic control and body weight in prediabetes and diabetic patients began at the first month postoperatively and persisted in the next 12 months. This result corresponded with the findings of Rubio-Almanza et al, who suggested that bariatric surgery improves glycaemic control and obesity comorbidities in prediabetes patients [ 22 ]. In addition, nearly 70% of prediabetes cases in our centre were treated by LSG.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Improvement in glycaemic control and body weight in prediabetes and diabetic patients began at the first month postoperatively and persisted in the next 12 months. This result corresponded with the findings of Rubio-Almanza et al, who suggested that bariatric surgery improves glycaemic control and obesity comorbidities in prediabetes patients [ 22 ]. In addition, nearly 70% of prediabetes cases in our centre were treated by LSG.…”
Section: Discussionsupporting
confidence: 91%
“…that bariatric surgery improves glycaemic control and obesity comorbidities in prediabetes patients [22]. In addition, nearly 70% of prediabetes cases in our centre were treated by LSG.…”
Section: Ast (U/l)mentioning
confidence: 77%
“…Improvement in glycaemic control and body weight in prediabetes and diabetic patients began at the rst month postoperatively and persisted in the next 12 months. This result corresponded with the ndings of Rubio-Almanza et al, who suggested that bariatric surgery improves glycaemic control and obesity comorbidities in prediabetes patients [22]. In addition, nearly 70% of prediabetes cases in our centre were treated by LSG.…”
Section: Discussionsupporting
confidence: 90%
“…Improvement of glycemic control and body weight in pre-diabetics and diabetics began at the rst month post-op and persisted in the next 12 months. This corresponded to Rubio-Almanza et al, who suggested that bariatric surgery improved glycemic control and obesity comorbidities in the pre-diabetes patient [22]. Besides, nearly 70% of pre-diabetics in our centre was treated by LSG.…”
Section: Discussionsupporting
confidence: 81%